An Analysis of Politeness Comments by Indonesian National Team Football Players on Governor Ganjar Pranowo’s Instagram - Ambarwati, Rosita; Ajeng Damayanti, Wahyu (KnE Social Sciences, 2024)
Politeness plays a crucial role in effective communication. A common challenge in communication is the expression of politeness on social media. This article examines the politeness strategies employed by Indonesian national football team players in their comments on Ganjar Pranowo’s Instagram post discussing Indonesia’s unsuccessful bid to host the U-20 World Cup. Brown and Levinson’s theory (1987) serves as the basis for analyzing the politeness strategy. The research follows a descriptive-qualitative approach. The study relies on netizens’ comments as the primary source of data. Data collection involves documentation methods and refer to note-taking procedures. This study involved a close examination of statements made by football national team players on Ganjar Pranowo’s Instagram account. The study results are (1) three types of positive politeness strategies, two types of negative politeness strategies, and two types of off-record strategies. Positive Politeness strategy 4: Exaggerate 2 (66.67%) and Joke 1 (33.33%). Regarding Negative Politeness, the analysis reveals 2 strategies: Be Pessimistic 1 (50%) and General Requirements 1 (50%). Off-record strategies include Contradictory 1 (50%) and Ironic 1 (50%). The Exaggerate type of Positive Politeness is assumed to be the most dominant, accounting for 2 (66.67%) instances. One can conclude that individuals demonstrate politeness when using social media. Keywords: Instagram post, politeness strategies, U-20 World Cup